2020
DOI: 10.3168/jdsc.2020-18587
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol deficiency carriers have lowered serum cholesterol and perform well at an elite cattle show

Abstract: In a small sample of carriers of cholesterol deficiency, the genetic disorder that affects low density lipoprotein transportation in Holstein cattle, serum cholesterol was lower than that of their herdmates. Furthermore, cows that inherited the cholesterol deficiency mutation from their sire placed in the top 5 of their classes at World Dairy Expo more often than their noncarrier paternal sisters. Highlights • Cholesterol deficiency carriers had lower serum cholesterol than noncarriers. • Cholesterol deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our transcriptomic data from the differential expression analysis confirm that the ERV-K LTR insertion indirectly affects the regulation of cholesterol synthesis in addition to its direct effect on APOB transcription. Earlier studies identified that CDC animals show a decreased plasma cholesterol level 11 , 12 . Gross et al 12 suggested that this results from a lack of APOB protein with the consequence of building less HDL, LDL and/or VLDL complexes containing cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our transcriptomic data from the differential expression analysis confirm that the ERV-K LTR insertion indirectly affects the regulation of cholesterol synthesis in addition to its direct effect on APOB transcription. Earlier studies identified that CDC animals show a decreased plasma cholesterol level 11 , 12 . Gross et al 12 suggested that this results from a lack of APOB protein with the consequence of building less HDL, LDL and/or VLDL complexes containing cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its molecular genetic background, also pathophysiological consequences of the CD mutation are controversially discussed 11 14 . Recent data challenge the recessive inheritance mode of CD.…”
Section: Introductionmentioning
confidence: 99%